PVC Sensors for Ciprofloxacin Based on Inclusion Complex with β - and γ-Cyclodextrin - AlRabiah, Haitham; Ezzeldin, Essam; Abounassif, Mohammed; Abdel-Hafiz Mostafa, Gamal (Current Pharmaceutical Analysis, 2018)
Purpose: To develop two PVC membrane sensors for determination of ciprofloxacin (CIP). Method: Beta - or γ-cyclodextrin was investigated as electroactive material for the formation of sensor 1 and 2 in the presence of potassium tetrakis (4-chlorophenyl) borate (KTpClPB) as ion additive. Results: The investigated sensors appeared fast, accurate, sensitive and showed near-Nernstian response (50 mV/ decade) with a calibration range for CIP (1 0-3 - 80-6 and 1 10-3 - 1.00-5 mol L-1). The detection limits were 90-6, and 80-6 mol L-1 for β- or γ- cyclodextrin sensor, respectively. The measuring pH of the developed sensors was in 3 - 6 range. Selectivity coefficient of the proposed methods indicates that both sensors showed a high selectivity for CIP in the presence of many ions and different common drug excipients. The proposed mechanism is based on inclusion complex or host-guest interaction. Conclusion: The advantages of the developed sensors are that it is accurate, selective, sensitive and cost less compared with published instrumental methods of analysis. The proposed sensors have been utilized for quantification of CIP in bulk and its formulation with good reproduicibilty compared with British pharmacopeia method.
Keywords: Ciprofloxacin